Promoting Environmental Sustainability Through Guerrilla Marketing - Donny SUSILO (International Journal of Environmental, Sustainability, and Social Science, 2020)
Environment becomes major concern for all countries throughout the world since Sustainable Development Goals were promoted. However the target is impossible to achieve without awareness and participation of the public. Promoting environmental sustainability is difficult and costly, therefore a breakthrough is required. The concept of guerrilla marketing has been widely used and recognized as low cost, but effective marketing strategy, therefore it is also an appropriate innovative way of promoting environmental sustainability in public area. This study explores the successful application of guerrilla marketing for promoting environmental sustainability around the world. Three case studies were chosen to figure out how it works. The successful applications confirm that guerrilla campaign for sustainability needs element of humour, uniqueness, sensation, creativity, surprise and education. Both profit and non-profit organizations can achieve their goal in both effective and efficient way when they know how to apply guerrilla marketing properly